Cyclohexanone-aniline-formaldehyde resins - synthesis and characterization - Mustata, F.; Bicu, I. (Polimery, 2022)
Cyclohexanone-aniline-formaldehyde resins, which contain functional groups in the polymeric chain, were prepared by acid catalysis condensation. Mixture of toluene and N- methylpyrrolidone was used both as reaction medium and as carrier for aqueous condensation. The resins were characterized by determination of melting points, viscosity measurement and elemental analysis (contents of nitrogen, N%). Their structure was established by means of IR and H-1 NMR spectroscopy. The obtained polymers have low molecular weights and a moderate solubility in medium and highly polar organic solvents. Thermal studies pointed out that these polymers undergo 2-5% weight loss up to 210degreesC for resins with low content of aniline, whereas weight loss starts at 220-240degreesC for resins with low content in cyclohexanone. Activation energy for the thermal degradation is observed to be within the range 37.6-41.7 kJ/mol.